Implementasi Pelatihan Petrologi Untuk Pengembangan Keterampilan Deskripsi Batuan Pada Siswa SMK Negeri 6 Kendari - Masri Masri; Ali Okto; Rio Irhan Mais Cendra Jaya; Hasria Hasria; Muliddin Muliddin; La Ode Sahiddin; Wa Ode Suwardi; Wa Ode Sitti Jumrana Atodding (Indonesian Journal Publisher, 2025)
A rock description training has been conducted at SMK Negeri 6 Kendari to enhance fundamental petrology knowledge and descriptive skills among students in the Mining Geology program. This training involved 47 senior-level students and was implemented through several stages, including preparation, material presentation, rock description practicum, and outcome evaluation via written exam and analytical rubric assessment. The training comprised theoretical and practical sessions focused on the description of three rock groups (igneous, sedimentary, and metamorphic) using hand specimens and thin sections. The analysis demonstrates a significant enhancement in students' comprehension, as reflected in the increase in the average post-test score to 62.02, compared to the pre-test score of 45.74. An improvement in descriptive skills was also evident based on the evaluation rubric, with a greater number of students achieving the